1966
DOI: 10.1113/jphysiol.1966.sp008022
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological study of odour similarities of homologous substances

Abstract: SUMMARY1. The activity of single bulbar units in the olfactory system of the frog was recorded extracellularly by means of micro-electrodes. The electroolfactogram was recorded simultaneously from the receptor epithelium.2. The olfactory epithelium was stimulated with substances of homologous series of normal aliphatic alcohols, acetates and ketones.3. The effect on a bulbar unit was classified as excitatory or inhibitory, and the chi-square values calculated with one degree of freedom for all pairs in a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1967
1967
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…The response patterns of single cells to various odorants either in the gaseous phase or in the aqueous one were studied in the olfactory bulb by many investigators (SHIBUYA et al, 1962;DOVING, 1965DOVING, , 1966aDOVING et al 1974;HARA, 1967HARA, , 1975HIGASHINO et al, 1969;MATHEWS 1972a, b;TANABE et al, 1975;SHIBUYA et al, 1977). In the present experiment, odorous substances of the same concentrations were applied in the gaseous and aqueous phases, and the stimulative effects were compared.…”
Section: Discussionmentioning
confidence: 99%
“…The response patterns of single cells to various odorants either in the gaseous phase or in the aqueous one were studied in the olfactory bulb by many investigators (SHIBUYA et al, 1962;DOVING, 1965DOVING, , 1966aDOVING et al 1974;HARA, 1967HARA, , 1975HIGASHINO et al, 1969;MATHEWS 1972a, b;TANABE et al, 1975;SHIBUYA et al, 1977). In the present experiment, odorous substances of the same concentrations were applied in the gaseous and aqueous phases, and the stimulative effects were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in hydrocarbon structure, especially in carbon chain length, allow facile comparisons between odorant structure and either neural activity or behavior (Döving, 1966;Mori et al, 1992;Imamura et al, 1992;Sato et al, 1994;ComettoMuñ iz et al, 1998;Laska and Teubner, 1998;Laska et al, 1999;Johnson et al, 1999;Malnic et al, 1999;Rubin and Katz, 1999). In the present study, we exposed animals to the five odorants shown in Table 1.…”
mentioning
confidence: 95%
“…Because very closely related chemicals evoke the perception of distinct odors, it remains necessary to address how such similar odorants are coded by the mammalian nervous system. A powerful choice for such studies involves homologous series of odorants differing by single steps of carbon chain length but possessing the same functional chemical group (Döving, 1966;Mori et al, 1992;Imamura et al, 1992;Sato et al, 1994). By using homologous series of aliphatic acids and other aliphatic carbonyl-containing compounds, individual mitral/tufted cells in the dorsomedial rabbit olfactory bulb were found to be tuned to odorants possessing a limited range of carbon chain lengths Imamura et al, 1992).…”
mentioning
confidence: 99%